Will they co-crystallize?. Issue 36 (12th July 2017) - Wicker, Jerome G. P.; Crowley, Lorraine M.; Robshaw, Oliver; Little, Edmund J.; Stokes, Stephen P.; Cooper, Richard I.; Lawrence, Simon E.
Abstract : Co-crystal screening data and machine learning models allows prediction of the most likely co-formers to use for new molecules. Abstract : A data-driven approach to predicting co-crystal formation reduces the number of experiments required to successfully produce new co-crystals. A machine learning algorithm trained on an in-house set of co-crystallization experiments results in a 2.6-fold enrichment of successful co-crystal formation in a ranked list of co-formers, using an unseen set of paracetamol test experiments.